2020
DOI: 10.3390/membranes10070156
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Design as a Tool for Optimizing and Predicting the Nanofiltration Performance by Treating Antibiotic-Containing Wastewater

Abstract: In recent years, there has been an increase in studies regarding nanofiltration-based processes for removing antibiotics and other pharmaceutical compounds from water and wastewater. In this work, a 2k factorial design with five control factors (antibiotic molecular weight and concentration, nanofiltration (NF) membrane, feed flow rate, and transmembrane pressure) was employed to optimize the NF performance on the treatment of antibiotic-containing wastewater. The resulting multiple linear regression model was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Over the last three decades, the occurrence of pharmaceutical compounds in the environment, as well as the different solutions aimed at removing these compounds from wastewater, thus preventing them from reaching the environment, have been the central theme of numerous scientific articles [1][2][3][4]. Among these solutions are treatments by advanced oxidative processes [5][6][7], membrane filtration technologies [8][9][10], biological processes [11][12][13], and combined processes [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last three decades, the occurrence of pharmaceutical compounds in the environment, as well as the different solutions aimed at removing these compounds from wastewater, thus preventing them from reaching the environment, have been the central theme of numerous scientific articles [1][2][3][4]. Among these solutions are treatments by advanced oxidative processes [5][6][7], membrane filtration technologies [8][9][10], biological processes [11][12][13], and combined processes [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The pH of the feed influenced the membrane surface charge, permeate flux and retention of individual compounds. Polyamide membranes have an isoelectric point at pH 3.5–4.0, at which maximum permeate flux and the highest permeability occurred [ 53 ]. If the pH is higher than the isoelectric point, a negative charge increase will occur on the membrane surface increasing ion rejection [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…If the pH is closer to the isoelectric point of a membrane, the retention of bioactive compounds will decrease [ 54 ]. The isoelectric point of polyamide membranes is usually at pH 3.5 to 4.0 [ 55 ], and the pH values of conventional and ecological wine used in this study were 3.92 and 3.75, respectively. Furthermore, Arsuaga et al [ 56 ] reported that the retention of the phenolic compounds depended on their adsorption on nanofiltration membranes.…”
Section: Discussionmentioning
confidence: 99%